The Correlation between Self-Regulation Learning and Listening Comprehension of the Eleventh Grade Students - Desi Yulianti (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2020)
This research aimed to describe the correlation between self-regulation and listening comprehension. The method which was used in this research was correlational research. The population of the research was the eleventh grade students of SMA Muhammadyah 2 Palembang. There were 105 students from four classes as the population in this research. The sample was taken by using a total sampling which consists of 99 students. Furthermore, there were two variables in this research. The first one was self-regulation (variable X) and the second one was listening comprehension (variable Y). The self-regulation score was taken from the MSLQ questionnaire whereas the student’ comprehension in listening was taken from TOEFL Junior descriptive statistics for the MSLQ and listening comprehension. Based on Pearson Product Moment Correlation Coefficient, the result indicated that the pattern of correlation between self-regulation and listening comprehension was negative. The correlation coefficient or the r-obtained (.300) was higher than r-table (.0.1663). Then, the level of probability (p) significance (sig.2-tailed) was .003. It means that p (0.03) was lower than .05. Thus, there was a significant correlation between the self-regulation and listening comprehension.